2010
DOI: 10.1007/s12369-010-0074-7
|View full text |Cite
|
Sign up to set email alerts
|

Would Children Help a Robot in Need?

Abstract: Just as human-human behavior and interactions are important to study, human-robot interactions will take more prominence in the near future. These interactions will not only be in one direction, robots helping humans, but they will also be bidirectional with humans helping robots. This study examined the interactions between children and robots by observing whether children help a robot complete a task, and the contexts which elicited the most help. Five studies were conducted each consisting of 20 or more chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…It was approved by the university's Conjoint Health Research Ethics Board. Most children in this study also participated in another project on children's helping behaviors towards a robot (Beran et al, 2011). We found no significant differences in perceptions of animism across the conditions used in the helping study or any relationship with helping behaviors.…”
Section: Sample and Proceduresmentioning
confidence: 61%
“…It was approved by the university's Conjoint Health Research Ethics Board. Most children in this study also participated in another project on children's helping behaviors towards a robot (Beran et al, 2011). We found no significant differences in perceptions of animism across the conditions used in the helping study or any relationship with helping behaviors.…”
Section: Sample and Proceduresmentioning
confidence: 61%
“…Similarly, children are naturally inclined to help a "robot in need" when it displays distressed behavior, although the extent of helping depends on how the child was introduced to the robot [Beran and Ramirez-serrano 2011;Beran et al 2010]. Interestingly, researchers may leverage such principles by presenting a robot as a less-knowledgeable other, to whom the child provides caregiving behavior [Tanaka and Matsuzoe 2012] or whom they teach [de Greeff and Belpaeme 2015;Hood et al 2015].…”
Section: Cal Systems Enhanced With Social Robotsmentioning
confidence: 99%
“…They help same-aged peers (Hepach et al, 2017), familiar (e.g., Tomasello, 2006, 2007;Allen et al, 2018) and unfamiliar adults (Rheingold, 1982;Hepach et al, 2016), and even recipients who had behaved antisocially (Dahl et al, 2013;Sebastián-Enesco et al, 2013;c.f., Vaish et al, 2010). Furthermore, a recent study showed that young children's helping behavior is not confined to human recipients, but extends to a robot in need (Martin et al, 2020; for a study with older children, see Beran et al, 2011). In particular, using a procedure based on research by Tomasello (2006, 2007), Martin et al (2020) presented 3-year-old children with a humanoid robot that played a xylophone and subsequently dropped the xylophone stick out of its reach.…”
Section: Introductionmentioning
confidence: 99%